Directed Evolution of Pseudomonas fluorescens Lipase Variants With Improved Thermostability Using Error-Prone PCR - Guan, Lijun; Gao, Yang; Li, Jialei; Wang, Kunlun; Zhang, Zhihong; Yan, Song; Ji, Nina; Zhou, Ye; Lu, Shuwen (Frontiers in Bioengineering and Biotechnology, 2020)
Lipases catalyze the hydrolysis of fats and oils, and have been widely used in various industrial fields. However, bacterial lipases have a lower thermostability in industrial processes, which was a limiting factor in their industrial application. In this study，In this study, we obtained an improve variant of Pseudomonas fluorescens lipase (PFL) with enhanced thermostability using classical error-prone PCR. Wild-type PFL showed an optimal temperature and pH of 50 °C and pH 7.5, respectively. Due to the low thermostability of PFL, a library containing over 3000 individual mutants as constructed using error-prone PCR. Screening for thermotolerance yielded the mutants L218P and P184C/M243C with Tm values of 62.5 and 66.0 °C, which was 2.5 and 6 °C higher than that of the WT, respectively. The combination of the two mutants (P184C/M243C/L218P) resulted in an approximately additive effect with a Tm value of 68.0 °C. Although the increase of Tm was not substantial, the mutant also had dramatically increased methanol tolerance. A mutant variant of PFL with higher thermostability was obtained by error-prone PCR. Structural analysis revealed that the introduction of a disulfide bond between P184C and M243C and the substitution of Pro to reduce the flexibility of a loop increased the thermostability of PFL, which provides a theoretical foundation for improving the thermostability and methanol tolerance of lipase family I.1 to resist the harsh conditions of industrial processes.